INCREASING SOIL FERTILITY AND IMPROVING THE RECLAMATION CONDITION BY LOWERING THE GROUNDWATER LEVEL (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
The article presents the results of studies of highly moistened irrigated garden-meadow and meadow soils, a decrease in the groundwater level, and an increase in their fertility. According to the obtained data on soil salinization in the Peshku district, 79.5% of irrigated soils from the total area of arable land is subject to salinization, which are classified as slightly, moderately and strongly saline. To improve the ameliorative state of soils, mulberry plantations should be introduced into practice, which help reduce excessive moisture on the soil surface.